Thermodynamic calculation and analysis for aluminum‐alloyed high boron high speed steel: Thermodynamische Berechnungen und Analyse für aluminiumlegierte hochborhaltige Schnellarbeitsstähle. Issue 1 (30th January 2018) - Yang, Y.W.; Fu, H.G.; Wang, K.M.; Zhu, L.L.; Jang, L.
Abstract: The equilibrium solidified phase diagrams of high boron high speed steel have been calculated and the vertical section of iron‐carbon pseudo‐binary phase diagrams has been drawn with different aluminum concentration. The effect of aluminum on phase diagrams and solidification microstructure has been investigated by using optical microscope, scanning electron microscopy, X‐ray diffraction, and differential scanning calorimetry. The results show that the austenite region shrinks to a small area and the δ ‐iron changes into α‐iron directly during cooling process when the aluminum content reaches 1.5 wt.%. The addition of excessive amount of aluminum favors the formation of ferrite, which leads to the hardness decreasing. Moreover, excessive amount of aluminum (Al≥1.5 wt.%) will make network M2 B borocarbides tend to break. Alloying with aluminum raises the solubility of carbon in the matrix and reduces the quenched hardness. The calculation results are agreed with the ones from experimental. The calculation of phase diagrams method has been successfully used for the computation of phase equilibrium in the multi‐component high boron high‐speed steel system. The work provides a practical method for engineers and researchers in related areas.